Forensic Examination of Ear Morphology and Earprint of Malay Students in USM Health Campus - Nawaltul Akma, Ahmad Sabri (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
Human ear was first used for identification purposes in the late of 19th century. However, due to lack of research, this evidence has been taken for granted. Earprint, has long been overshadowed by the popularity of fingerprint. The purpose of this study is to characterize human ears for classification purposes as well as to assess the evidential value of earprint in forensic investigation. This research was carried out in two phases. In the first phase of this study, photos of right ear of the subjects (both female and male) were collected and class characteristics of the external ears have been determined. Eighty Malay students of USM Health Campus were used as subjects in this study. Results reveal some characteristics are observed to be common in examined subjects. The second phase of this study focuses on earprint. This phase is divided into three tests; surface test, ageing test and earprint profile test. The earprints developed by powdering technique were collected and compared against the photos of the ears in order to examine the 'presence' and 'absence' of characteristics as well as to figure out the factors that may contribute to this situation. Results show that glass and aluminum surfaces produce earprint of good quality and the quality of the aged earprint decreases as the time increases. The terms good and poor earprint shedder are used to classify the earprint profile of an individual. Most of the earprints in this study belong to poor earprint shedder. This research has demonstrated the potential use of earprint as evidence in forensic investigation.